The impact of foetal restrictions on mode of delivery in women with inherited bleeding disorders. (14th July 2020) - Lavin, Michelle; Horan, Maebh; Durand O'Connor, Anna; Doherty, Dearbhla; Manning, Catherine; Lynch, Caoimhe; Regan, Carmen; Ryan, Kevin; Byrne, Bridgette
Abstract: Objectives: Management of pregnancy in women with congenital bleeding disorders (CBD) is challenging and requires understanding of risks conferred to both the mother and the foetus. Some elements of labour management are considered to increase the risk of neonatal bleeding and are not recommended for neonates at risk of a significant bleeding disorder. The impact of these restrictions on obstetric outcomes in women with CBD is unknown. Methods: We retrospectively reviewed obstetric outcomes in a large cohort of women with CBD attending a specialised obstetric/haematology antenatal clinic over a 6‐year period. Results: Ninety‐four pregnancies in 76 women with a wide variety of CBDs were assessed. Foetal precautions were recommended in the majority of cases (88%). Twenty (21.2%) were delivered by elective Caesarean section (CS), predominantly for obstetric indications. Of the 63 women who laboured with foetal precautions in place, 6 (10%) had a CS that was performed because of these precautions. There was no neonatal bleeding but primary postpartum haemorrhage (PPH) occurred in 12.2% of women. Conclusions: These data show that foetal precautions in labour recommended for women with CBDs will influence mode of delivery in approximately 10% of cases. This is important information for counselling these women about labour and delivery.